Integrated monitoring in mobile devices - Grego, João Pedro Madail (2020)
With the increase of mobile device’s users, and the consequent decline of the computer as the main way of accessing the internet, the number of attacks on mobile devices rose considerably. Furthermore, these devices became more and more diverse and complex, resulting in a modern phone that has several possible attack vectors. But not only digital events threaten the user of these machines, and they can even be a plus in the detection and reduction of the impact of physical dangers. This work explores a way of limiting the effect of digital attacks and, simultaneously, try to detect physical events that may menace the phone’s bearer. Besides this dissertation, this work also resulted in an application for Android, with the source code published in GitHub with a free and open license.